Preparation method of MXene / covalent organic framework double-layer aerogel
Through the combination of directional refrigeration technology and MXene coating, the agglomeration and porosity of COFs materials in functional devices are solved, and the MXene/COF double-layer aerogel with high mechanical properties and multi-stage structure is realized, which improves its Application potential in the field of solar seawater desalination.
Patent Information
- Application Number
- CN202411510870.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2024-12-31
AI Technical Summary
The application of existing covalent organic framework (COFs) materials in functional devices is limited by agglomeration, insufficient pore complexity, poor mechanical properties, and inherent hydrophobicity and narrow spectral absorption range, making it difficult to achieve efficient solar energy conversion and seawater desalination.
Directional refrigeration technology is used to prepare MXene/covalent organic frame double-layer aerogel, adjust the hydrophilicity and mechanical properties of TpS-COF hydrogel through diamine linkers, and deposit MXene coating on its surface to build an arrangement channel multi-level structure of large and small pores.
The formation of an orderly internal structure of COF-based hydrogel has been achieved, the material transmission efficiency and mechanical properties have been improved, its application potential in the field of solar seawater desalination has been expanded, and the functionality and universality of the material have been improved.
Smart Images

Figure CN119219970A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a MXene / covalent organic framework double-layer aerogel, and belongs to the technical field of covalent organic framework preparation. Background Art
[0002] Covalent organic frameworks (COFs) have attracted great interest as porous materials due to their rich building blocks, adjustable covalent networks, and excellent chemical and thermal stability. They are potential new platforms for the development of functional devices. At present, research on COFs mainly focuses on the application of COFs powders or films in related functional fields. For example, in mass transport devices, when used as powders, the strong π-π stacking and van der Waals forces between particles can easily lead to COFs agglomeration, reducing binding points and adsorption capacity. Compared with particles, films have more uniform porosity and shorter transmission paths, but the lack of pore complexity limits the further improvement of mass transport and diffusion; the processability and mechanical properties of particles and films are poor, which is not conducive to the construction of multi-level COFs structures for use in functional devices.
[0003] Therefore, the development of bulk COFs (foams, hydrogels, aerogels, etc.) with hierarchical porous macroscopic three-dimensional (3D) structures and ideal mechanical strength is very important for expanding the application of COFs in functional devices. Hydrogels or aerogels are ideal matrices for constructing 3D COFs due to their wide pore size distribution, high specific surface area, customizable chain structure and macroscopic network. Therefore, COFs-based hydrogels / aerogels have attracted increasing attention in recent years. It has been shown that the nanoparticles / nanofibers formed during the polycondensation process form COF nanosheets through growth or cross-linking, and then the stacking / aggregation of nanosheets leads to the formation of a gel network structure, which can be locked by the strong interaction between the abundant hydrogen donor and acceptor groups in the nanosheets. Compared with powders and films, bulk COFs have superior processability and good self-supporting structure, making them excellent carriers for functional devices. For example, the presence of microporous and mesoporous structures can improve the adsorption capacity of organic or inorganic chemicals, and the continuous porosity and adjustable pore size are beneficial for the transport of water or oil.
[0004] Gel materials with three-dimensional pore structures are excellent carriers that take advantage of the COF mesoporous structure and can simultaneously construct multi-level structures of micropores and mesopores / macropores. However, the disorder of the internal pores of the gel limits the transport rate of substances to a certain extent. If the COF-based hydrogel can be endowed with an orderly oriented structure, the transmission path of the substance will be shortened, the transmission efficiency will be improved, and the utilization rate of its internal porous structure will be increased. In addition, the inherent hydrophobicity and narrow spectral absorption range (near-infrared region) of COF materials seriously limit their development in the field of solar thermal conversion. If only pure COF materials are used to achieve higher solar energy conversion efficiency or desalination performance, there are problems such as limited raw material selectivity, difficult synthesis process and high cost, and it is difficult to open up the functional application market of COF materials. Therefore, developing COF-based composite materials to endow them with specific functional applications is a promising strategy. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing a MXene / covalent organic framework double-layer aerogel. The method uses a directional freezing technique to prepare a double-layer COF-based aerogel with arranged channels and coexisting large and small pores. The small pores are mainly present in the lower COF gel part, and the large pores are mainly present in the top MXene coating. The length of the aromatic chain of the diamine linker is used to adjust Tp S -COF hydrogel's hydrophilicity, specific surface area, morphology and overall mechanical properties. In addition, the preparation of MXene coatings provides more functional possibilities and universality for most basic COF-based hydrogels or aerogels. For example, MXene coatings are conducive to the use of composite COF gel materials in the field of solar desalination.
[0006] The technical solution for achieving the purpose of the present invention is as follows: The preparation method of MXene / covalent organic framework double-layer aerogel, the specific steps are as follows: Step 1: 1,3,5-triformylphloroglucinol (Tp) and a diamine monomer protected by tert-butyloxycarbonyl (Boc) ( S- Boc) was synthesized by condensation polymerization β -Keto-enamine covalent organic framework organogel (Tp S -COF); Step 2: The Tp obtained by solvent exchange S -COF hydrogel was placed on a directional freezing device, and MXene dispersion was drop-casted on Tp S -COF hydrogel upper surface; Step 3: After the entire system is completely frozen along the temperature gradient, the sample is freeze-dried to obtain a double-layer aerogel with a MXene coating (MX-Tp S -COF).
[0007] In step 1, the diamine monomer ( S The amino group of the 2-hydroxy-2-nitropropene is protected by a tert-butyloxycarbonyl (Boc) group in order to deliberately slow down the polymerization rate of the polycondensation reaction. c direction to form interlayer π-π stacking.
[0008] In step 1, the aldehyde group of the small molecule Tp and S- Boc first undergoes a dehydration condensation reaction to form a covalent polymer network connected by imine bonds, and then undergoes a structural isomerization process to form a more stable keto-enamine covalent organic framework. In addition to a large amount of carbon elements on the main framework, the formed covalent organic framework also has N, O, and H elements evenly distributed at different contents, which provides the possibility for physical cross-linking (hydrogen bonds or electrostatic interactions) between covalent networks, resulting in the formation of COF-based hydrogels with excellent mechanical properties.
[0009] In step 1, the COF-based hydrogel component is a conventionally used COF matrix with strong affinity, such as β -Keto-enamine COF (Tp-COF). The formation of covalent organic framework organogels is mainly caused by the stacking or entanglement of nanoparticles / nanofibers during polycondensation to form COF nanosheets, and then the mutual stacking or aggregation of COF nanosheets to form a gel framework structure, or the interaction between COFs nanofibers / nanofibers and solvents promotes the formation of a 3D skeleton.
[0010] Preferably, in step 2, the MXene dispersion and Tp S -COF hydrogel as a complete system is placed on a directional freezing device using liquid nitrogen as a cold source. Selecting liquid nitrogen with a lower temperature as a cold source is conducive to the conduction and freezing of temperature from bottom to top. The prepared MXene dispersion is composed of MXene / bacterial cellulose (BC) suspension. The high molecular weight long chain of bacterial cellulose and MXene nanosheets interact through hydrogen bonds to form a highly stable MXene coating, so that the structure of the MXene coating will not decompose and collapse under high temperature conditions.
[0011] Preferably, in step 3, the sample is freeze-dried in a freeze dryer for 24 hours to obtain a double-layer aerogel (MX-Tp S -COF).
[0012] In this invention, Tp-COF with good affinity performance is used as the research object, and the selected diamine linkers are diamino monomers with different aromatic chain lengths. The three diamine monomers are 1,4-phenylenediamine (Pa), 4,4'-diphenylenediamine (BD) and 4,4'-p-phenylenediamine (DT). The linker chain length is increased from one aromatic ring to three aromatic rings, which is intended to regulate Tp by changing the aromatic chain length (number of aromatic rings). S -COF hydrogel's hydrophilicity, specific surface area, morphology and structure, as well as its overall mechanical properties.
[0013] Furthermore, a specific preparation method of the TpS-COF organogel in step 1 is as follows: First, various diamine monomers (5 mmol) were mixed with di-tert-butyl dicarbonate (20.00 mmol) in tetrahydrofuran (100 mL) solvent and stirred at room temperature for 24 hours. S- Boc, different diamine monomers correspond to Pa-(Boc)2, BD-(Boc)2, and DT-(Boc)2 respectively.
[0014] Then, S- Boc (0.15 mmol), Tp (0.1 mmol), 3.40 mL of dioxane and 0.60 mL of water were added to a 25.0 mL hydrothermal synthesis reactor, and ultrasonic reaction was performed for 10 minutes. 70 μL of trifluoroacetic acid (TFA) was added as a catalyst. The hydrothermal reactor was sealed and heated at 120 o C in an oven for 72 h to obtain Tp S -COF organogels.
[0015] Further, the Tp of step 2 was obtained by multiple solvent exchanges with ethanol and deionized water. S -COF hydrogel.
[0016] Then Tp S -COF hydrogel was placed on the copper plate of the directional freezing device. At the beginning of directional freezing, MXene / bacterial cellulose (BC) suspension (MXene / BC = 20:1 w / w, 20 mg mL −1 ) evenly drop on Tp S -COF hydrogel surface. Finally, the sample was freeze-dried for 24 h to obtain MX-Tp S -COF double-layer aerogel.
[0017] Compared with the prior art, the present invention has the following advantages: (1) The present invention uses directional freezing technology to simultaneously endow COF-based hydrogels and MXene coatings with directional macroporous channels. This technology achieves the simultaneous construction of a multi-level structure of micropores and mesopores / macropores inside the COF-based hydrogel, which transforms the internal disordered structure into an ordered structure, which is beneficial to the rapid recognition and transmission of substances.
[0018] (2) The present invention is in Tp S In the -COF hydrogel system, the length of the aromatic chain of the diamine linker is used to adjust the hydrophilicity, specific surface area and morphology; at the same time, as the number of rigid aromatic rings increases, the hydrogel is given better mechanical properties.
[0019] (3) The present invention provides an attractive strategy for the rational design and construction of multiscale structures in bulk COFs by using directional freezing technology, namely, building multilayer structures inside and on the surface of COF aerogels, and also provides a promising strategy for integrating multiple functions into COF-based gel materials.
[0020] The MXene / covalent organic framework double-layer aerogel prepared by the present invention can be used in solar seawater desalination. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 (a) The molecular structure and physical pictures of hydrogels of Comparative Examples 1, 2, and 3, and (b) the water contact angle pictures of aerogels.
[0022] Figure 2 Scanning electron microscope images of aerogels prepared in comparative examples and examples, (ac) are comparative examples 1, 2, and 3, (df) are examples 1, 2, and 3, and the scale bar is 50 μm.
[0023] Figure 3 A summary of the pores and pore sizes of the prepared aerogels, (ac) are comparative examples 1, 2, and 3, and (d-) are examples 1, 2, and 3.
[0024] Figure 4 The mechanical properties diagram of the hydrogels prepared in Examples 1, 2, and 3.
[0025] Figure 5 It is a comparison chart of the salt removal capacity of Example 1 and Comparative Example 4 in solar seawater desalination applications.
[0026] Figure 6 The figure is a performance comparison chart of Examples 1, 2, 3 and Comparative Example 4 in solar seawater desalination applications. DETAILED DESCRIPTION
[0027] The present invention is further described in detail below in conjunction with specific embodiments and drawings. Example 1
[0028] (1) First, 1,4-phenylenediamine (Pa) (5 mmol) and di-tert-butyl dicarbonate (20.00 mmol) were mixed in tetrahydrofuran (100 mL) solvent and stirred at room temperature for 24 hours. White powder Pa-(Boc)2 was purified and the yield was 91%.
[0029] (2) Pa-(Boc)2 (0.15 mmol), Tp (0.1 mmol), 3.40 mL of dioxane and 0.60 mL of water were added to a 25.0 mL hydrothermal synthesis reactor, and ultrasonically reacted for 10 minutes. 70 μL of trifluoroacetic acid (TFA) was added as a catalyst and ultrasonically reacted for 5 minutes. The hydrothermal reactor was sealed and heated at 120 o The TpPa-COF organogel was obtained by reacting in an oven at 400 °C for 72 h. After multiple solvent exchanges with ethanol and deionized water, a cylindrical TpPa-COF hydrogel with a diameter of 2 cm was obtained.
[0030] (3) The TpPa-COF hydrogel was placed on the copper plate of the directional freezing device. At the beginning of directional freezing, 0.3 mL of MXene / bacterial cellulose (BC) suspension (MXene / BC = 20:1 w / w, 20 mg mL −1 ) was evenly dripped on the surface of TpPa-COF hydrogel. After the entire system was completely frozen along the temperature gradient direction (from bottom to top), the sample was freeze-dried for 24 hours to obtain a double-layer aerogel (MX-TpPa-COF) with MXene coating. Example 2
[0031] (1) First, 4,4'-benzyl diamine (BD) (5 mmol) and di-tert-butyl dicarbonate (20.00 mmol) were mixed in tetrahydrofuran (100 mL) solvent. After stirring at room temperature for 24 hours, light gray powder BD-(Boc)2 was purified with a yield of 89%.
[0032] (2) BD-(Boc)2 (0.15 mmol), Tp (0.1 mmol), 3.40 mL of dioxane and 0.60 mL of water were added to a 25.0 mL hydrothermal synthesis reactor, and ultrasonically reacted for 10 minutes. 70 μL of trifluoroacetic acid (TFA) was added as a catalyst and ultrasonically reacted for 5 minutes. The hydrothermal reactor was sealed and heated at 120 o The TpBD-COF organogel was obtained by reacting in an oven at 400 °C for 72 h. After multiple solvent exchanges with ethanol and deionized water, a cylindrical TpBD-COF hydrogel with a diameter of 2 cm was obtained.
[0033] (3) The TpBD-COF hydrogel was placed on the copper plate of the directional freezing device. At the beginning of directional freezing, 0.3 mL of MXene / bacterial cellulose (BC) suspension (MXene / BC = 20:1 w / w, 20 mg mL −1 ) was evenly dripped on the surface of TpBD-COF hydrogel. After the entire system was completely frozen along the temperature gradient direction (from bottom to top), the sample was freeze-dried for 24 hours to obtain a double-layer aerogel (MX-TpBD-COF) with MXene coating. Example 3
[0034] (1) First, 4,4'-p-phenylenediamine (DT) (5 mmol) and di-tert-butyl dicarbonate (20.00 mmol) were mixed in tetrahydrofuran (100 mL) solvent. After stirring at room temperature for 24 hours, white powder DT-(Boc)2 was purified and the yield was 88%.
[0035] (2) DT-(Boc)2 (0.15 mmol), Tp (0.1 mmol), 3.40 mL of dioxane and 0.60 mL of water were added to a 25.0 mL hydrothermal synthesis reactor, and ultrasonically reacted for 10 minutes. 70 μL of trifluoroacetic acid (TFA) was added as a catalyst and ultrasonically reacted for 5 minutes. The hydrothermal reactor was sealed and heated at 120 o The TpDT-COF organogel was obtained by reacting in an oven at 400 °C for 72 h. After multiple solvent exchanges with ethanol and deionized water, a cylindrical TpDT-COF hydrogel with a diameter of 2 cm was obtained.
[0036] (3) The TpDT-COF hydrogel was placed on the copper plate of the directional freezing device. At the beginning of directional freezing, 0.3 mL of MXene / bacterial cellulose (BC) suspension (MXene / BC = 20:1 w / w, 20 mg mL −1 ) was evenly dripped on the surface of TpDT-COF hydrogel. After the entire system was completely frozen along the temperature gradient direction (from bottom to top), the sample was freeze-dried for 24 hours to obtain a double-layer aerogel (MX-TpDT-COF) with MXene coating.
[0037] Comparative Example 1 (1) First, 1,4-phenylenediamine (Pa) (5 mmol) and di-tert-butyl dicarbonate (20.00 mmol) were mixed in tetrahydrofuran (100 mL) solvent and stirred at room temperature for 24 hours. White powder Pa-(Boc)2 was purified and the yield was 91%.
[0038] (2) Pa-(Boc)2 (0.15 mmol), Tp (0.1 mmol), 3.40 mL of dioxane and 0.60 mL of water were added to a 25.0 mL hydrothermal synthesis reactor, and ultrasonically reacted for 10 minutes. 70 μL of trifluoroacetic acid (TFA) was added as a catalyst and ultrasonically reacted for 5 minutes. The hydrothermal reactor was sealed and heated at 120 o The TpPa-COF organogel was obtained by reacting in an oven at 400 °C for 72 h. After multiple solvent exchanges with ethanol and deionized water, a cylindrical TpPa-COF hydrogel with a diameter of 2 cm was obtained.
[0039] (3) Place TpPa-COF hydrogel at −18 o The samples were placed in a refrigerator at 400 °C for 6 hours to ensure that the samples were slowly frozen. Then, the samples were freeze-dried for 24 hours to obtain TpPa-COF aerogel.
[0040] Comparative Example 2 (1) First, 4,4'-benzyl diamine (BD) (5 mmol) and di-tert-butyl dicarbonate (20.00 mmol) were mixed in tetrahydrofuran (100 mL) solvent. After stirring at room temperature for 24 hours, light gray powder BD-(Boc)2 was purified with a yield of 89%.
[0041] (2) BD-(Boc)2 (0.15 mmol), Tp (0.1 mmol), 3.40 mL of dioxane and 0.60 mL of water were added to a 25.0 mL hydrothermal synthesis reactor, and ultrasonically reacted for 10 minutes. 70 μL of trifluoroacetic acid (TFA) was added as a catalyst and ultrasonically reacted for 5 minutes. The hydrothermal reactor was sealed and heated at 120 o The TpBD-COF organogel was obtained by reacting in an oven at 400 °C for 72 h. After multiple solvent exchanges with ethanol and deionized water, a cylindrical TpBD-COF hydrogel with a diameter of 2 cm was obtained.
[0042] (3) Place TpBD-COF hydrogel at −18 o The samples were placed in a refrigerator at 400 °C for 6 hours to ensure that the samples were slowly frozen. Then, the samples were freeze-dried for 24 hours to obtain TpBD-COF aerogel.
[0043] Comparative Example 3 (1) First, 4,4'-p-phenylenediamine (DT) (5 mmol) and di-tert-butyl dicarbonate (20.00 mmol) were mixed in tetrahydrofuran (100 mL) solvent. After stirring at room temperature for 24 hours, white powder DT-(Boc)2 was purified and the yield was 88%.
[0044] (2) DT-(Boc)2 (0.15 mmol), Tp (0.1 mmol), 3.40 mL of dioxane and 0.60 mL of water were added to a 25.0 mL hydrothermal synthesis reactor, and ultrasonically reacted for 10 minutes. 70 μL of trifluoroacetic acid (TFA) was added as a catalyst and ultrasonically reacted for 5 minutes. The hydrothermal reactor was sealed and heated at 120 o The TpDT-COF organogel was obtained by reacting in an oven at 400 °C for 72 h. After multiple solvent exchanges with ethanol and deionized water, a cylindrical TpDT-COF hydrogel with a diameter of 2 cm was obtained.
[0045] (3) Place TpDT-COF hydrogel at −18 o The samples were placed in a refrigerator at 400 °C for 6 hours to ensure that the samples were slowly frozen. Then, the samples were freeze-dried for 24 hours to obtain TpDT-COF aerogel.
[0046] Comparative Example 4 (1) First, 1,4-phenylenediamine (Pa) (5 mmol) and di-tert-butyl dicarbonate (20.00 mmol) were mixed in tetrahydrofuran (100 mL) solvent and stirred at room temperature for 24 hours. White powder Pa-(Boc)2 was purified and the yield was 91%.
[0047] (2) Pa-(Boc)2 (0.15 mmol), Tp (0.1 mmol), 3.40 mL of dioxane and 0.60 mL of water were added to a 25.0 mL hydrothermal synthesis reactor, and ultrasonically reacted for 10 minutes. 70 μL of trifluoroacetic acid (TFA) was added as a catalyst and ultrasonically reacted for 5 minutes. The hydrothermal reactor was sealed and heated at 120 o The TpPa-COF organogel was obtained by reacting in an oven at 400 °C for 72 h. After multiple solvent exchanges with ethanol and deionized water, a cylindrical TpPa-COF hydrogel with a diameter of 2 cm was obtained.
[0048] (3) Place TpPa-COF hydrogel at −18 o The samples were placed in a refrigerator at 400 °C for 6 hours to ensure that the samples were slowly frozen. Then, the samples were freeze-dried for 24 hours to obtain TpPa-COF aerogel.
[0049] (4) Place the TpPa-COF aerogel on a glass plate and directly use a spray bottle to spray the MXene / bacterial cellulose (BC) suspension (MXene / BC = 20:1 w / w, 20 mg mL −1 ) was evenly sprayed on the surface of TpPa-COF aerogel. To ensure the thickness and uniformity of the aerogel surface coating, the coating was sprayed once every half an hour for a total of 3 times, and the sample surface was naturally air-dried.
[0050] Figure 1(a) Molecular structures and physical pictures of hydrogels of Comparative Examples 1, 2, and 3, and (b) water contact angle pictures of aerogels. Figure 1 a shows the molecular structures of three different linkers and the complete cylindrical Tp S -COF hydrogel, which shows that the present invention successfully synthesized COF-based hydrogel. S -COF aerogels have similar molecular structures and multilayer porous structures, but their hydrophilic properties vary due to the different carbon contents in their skeletons. Figure 1 The surface contact angle test of b proves this point. The water contact angles of the three samples are quite different, which are 34 o (Comparative Example 1), 52 o Comparative Example 2) and 67 o (Comparative Example 3), Tp S The hydrophilicity of -COFs decreases with increasing length of the aromatic linker. This trend is reasonable because when the chain length of the linker increases, Tp S More aromatic rings in the -COFs skeleton are exposed, resulting in fewer adsorption sites for water molecules.
[0051] Figure 2 The SEM images of the aerogels prepared in the comparative examples and the examples are shown in Figure 2. (ac) are comparative examples 1, 2, and 3, and (df) are examples 1, 2, and 3. The scale bar is 50 μm. It can be clearly seen from the SEM images of comparative examples 1, 2, and 3 that Tp S -COFs have a porous framework structure similar to a honeycomb. This porous structure is due to the fact that Boc protection slows down the polymerization reaction rate, thus facilitating the COF nanofibers / nanoparticles to form a porous framework structure. c Directional growth forms interlayer π-π stacking, resulting in the self-assembly of COF nanosheets formed by stacking or interconnection of nanoparticles / nanofibers. As expected, there are arranged pores with a wide size distribution inside the COF gels of Examples 1, 2, and 3, which are formed along the temperature gradient direction during the directional freezing process.
[0052] Figure 3 The pores and pore sizes of the prepared aerogels are summarized in Figures 1-4, (ac) for comparative examples 1, 2, and 3, and (d-) for embodiments 1, 2, and 3. It can be seen from the figure that the average pore size of comparative examples 1, 2, and 3 is 8-35 μm, and the average pore size of embodiments 1, 2, and 3 is 10-40 μm. This result shows that the directional freezing technology can successfully construct an ordered channel similar to a capillary channel inside the disordered COF-based gel. Obviously, the ordered structure inside the COF aerogel is conducive to the MX-Tp S -COF is used as a seawater evaporator.
[0053] Figure 4 The mechanical properties of the hydrogels prepared in Examples 1, 2, and 3 are shown in the figure. It can be seen from the figure that the three aerogels have a certain recovery ability after compression. However, with the increase of the rigid unit length, the hysteresis work of the first cycle increases significantly, and the overlap of the subsequent cycle trajectories deteriorates. Among the three aerogels, Example 1 has the best structural stability within the applied strain range, and since the ultimate stress decreases in each cycle, the network of Example 3 gradually collapses with cyclic compression. This shows that the increase in the chain length of the aromatic linker is not conducive to the close stacking of COF nanosheets, thereby leading to the degradation of the macro-scale hydrogel skeleton.
[0054] Figure 5 The figure is a comparison chart of the salt removal capacity of Example 1 and Comparative Example 4 in the application of solar desalination. It can be clearly seen from the SEM images of Example 1 and Comparative Example 4 that the morphology of the MXene coating is significantly different. The MXene coating of Comparative Example 4 is formed by disordered stacking of MXene nanosheets. In addition to the irregular arrangement of the pores in the coating itself, it may also block the lower COF gel channel. However, in Example 1, the MXene coating has regularly arranged directional macroporous channels with an average size of 20~65μm. Therefore, the multi-level structure in which the macroporous structure (surface MXene coating) and the small pore structure (lower COF gel matrix) coexist in Example 1 is conducive to the MX-Tp S -COF is used as a seawater evaporator. COF gel can ensure water supply and water storage at the same time, which is conducive to the enrichment of seawater; the local ordered containers formed on the surface of the MXene coating are distributed on the pores, which can serve as a reservoir and drainage layer for concentrated seawater at the same time, which is conducive to water evaporation and salt removal. Figure 5 b, c and Figure 5 e, f verified this conclusion. Example 1 and Comparative Example 4 were subjected to a 4-hour solar desalination simulation in 10% salt water. The results showed that there was almost no salt deposition on the surface of Example 1, while there was a large amount of salt deposition on the surface of Comparative Example 4.
[0055] Figure 6 The performance comparison chart of Examples 1, 2, 3 and Comparative Example 4 in solar desalination applications. In a windless environment with constant temperature (25°C) and constant humidity (30%), the evaporation performance was evaluated using brine with different salt concentrations. The evaporation rates are from large to small in the order of Example 1> Example 2> Example 3> Example 4, and it can be seen that Example 1 has the best evaporation performance. In summary, the arranged pore structure is crucial for water transfer and salt exchange, because the evaporation rate of the double-layer aerogel of Comparative Example 4 that has not been directional frozen is much lower than that of the aerogel with an arranged structure, especially at higher salt concentrations. Obviously, compared with the random pore structure with higher structural distortion, the directional pore structure is more conducive to the transport of seawater to the evaporation surface.
[0056] The present invention is not limited to the above-mentioned embodiments. On the basis of the technical solution disclosed in the present invention, technicians in this field can make some substitutions and deformations to some technical features therein according to the disclosed technical content without creative labor, and these substitutions and deformations are all within the protection scope of the present invention.
Claims
1. A method for preparing a MXene / covalent organic framework double-layer aerogel, characterized in that: The steps include: S1, synthesized by condensation polymerization of 1,3,5-triformylphloroglucinol and diamine monomer protected by tert-butyloxycarbonyl β -Keto-enamine covalent organic framework organogel; S2, placing the β-keto-enamine covalent organic framework hydrogel obtained by solvent exchange on a directional freezing device, and simultaneously drop-casting the MXene dispersion on the upper surface of the β-keto-enamine covalent organic framework hydrogel; S3, after the entire system is completely frozen along the temperature gradient direction, the sample is freeze-dried to obtain a double-layer aerogel with a MXene coating, which is the target product MXene / covalent organic framework double-layer aerogel.
2. The method for preparing the MXene / covalent organic framework double-layer aerogel according to claim 1, characterized in that: In step S1, the aldehyde group of 1,3,5-triformylphloroglucinol and the diamine monomer protected by tert-butyloxycarbonyl first undergo a dehydration condensation reaction to form a covalent polymer network connected by imine bonds, and then undergo a structural isomerization process to form a more stable keto-enamine covalent organic framework. The formation of the covalent organic framework organogel is caused by the stacking or entanglement of nanoparticles / nanofibers during the polycondensation process to form COF nanosheets, and then the COF nanosheets stack or aggregate to form a gel framework structure, or the interaction between COF nanofibers / nanofibers and solvents promotes the formation of a 3D skeleton, thereby forming a covalent organic framework organogel.
3. The method for preparing the MXene / covalent organic framework double-layer aerogel according to claim 1, characterized in that: In step S2, the MXene dispersion and the β-keto-enamine covalent organic framework hydrogel are placed as a complete system on a directional freezing device using liquid nitrogen as a cold source.
4. The method for preparing the MXene / covalent organic framework double-layer aerogel according to claim 1, characterized in that: In step S3, the sample is freeze-dried in a freeze dryer for 24 hours to obtain a double-layer aerogel with a MXene coating.
5. The method for preparing the MXene / covalent organic framework double-layer aerogel according to claim 1, characterized in that: In step S1, the diamine monomer is any one of 1,4-phenylenediamine, 4,4'-biphenylenediamine and 4,4'-p-phenylenediamine.
6. The method for preparing the MXene / covalent organic framework double-layer aerogel according to claim 5, characterized in that Step S1 is specifically divided into the following steps: S1-1, a diamine monomer and di-tert-butyl dicarbonate are mixed in tetrahydrofuran solvent, stirred at room temperature for 24 hours, and purified to obtain a diamine monomer protected by tert-butyloxycarbonyl group. S- Boc; S1-2, S- Boc, 1,3,5-triformylphloroglucinol, dioxane and water were added into the hydrothermal synthesis reactor respectively, ultrasonically reacted for 10 min, trifluoroacetic acid was used as catalyst, the hydrothermal reaction was sealed, and the reaction was carried out in an oven at 120 ° C for 72 h to obtain β-keto-enamine covalent organic framework organogel.
7. The method for preparing the MXene / covalent organic framework double-layer aerogel according to claim 6, characterized in that: The hydrophilicity, specific surface area, morphology and overall mechanical properties of the prepared β-keto-enamine covalent organic framework hydrogel can be adjusted by changing the aromatic chain length of the diamine linker.
Citation Information
Cited By
Preparation method of covalent organic framework-polymer mechanical interlocking structure hydrogel
CN120059070A
A method for preparing a covalent organic framework-polymer mechanically interlocked structure hydrogel
CN120059070B